2012 IEEE International Solid-State Circuits Conference 2012
DOI: 10.1109/isscc.2012.6177064
|View full text |Cite
|
Sign up to set email alerts
|

A 2.5D integrated voltage regulator using coupled-magnetic-core inductors on silicon interposer delivering 10.8A/mm<sup>2</sup>

Abstract: Energy consumption is a dominant constraint on the performance of modern microprocessors and systems-on-chip. Dynamic voltage and frequency scaling (DVFS) is a promising technique for performing "on-the-fly" energy-performance optimization in the presence of workload variability. Effective implementation of DVFS requires voltage regulators that can provide many independent power supplies and can transition power supply levels on nanosecond timescales, which is not possible with modern board-level voltage regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 4 publications
0
35
0
Order By: Relevance
“…Moreover, it supports the fine-grained voltage and frequency management and better power delivery efficiency. There have been attempts to embed voltage regulators on chips to support fine-grained voltage management [9], and a voltage regulator stacked in 2.5D has been demonstrated [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it supports the fine-grained voltage and frequency management and better power delivery efficiency. There have been attempts to embed voltage regulators on chips to support fine-grained voltage management [9], and a voltage regulator stacked in 2.5D has been demonstrated [10].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it supports the fine-grained voltage and frequency management and better power delivery efficiency. There have been attempts to embed voltage regulators on chips to support fine-grained voltage management [9], and a voltage regulator stacked in 2.5D has been demonstrated [10].In this paper, a thermal-aware VI formation for 3D manycore processors is proposed. A VI formation for many-core processors includes a series of procedures to decide on which core a task is mapped and a proper supply voltage for a core.…”
mentioning
confidence: 99%
“…Also, increased chip area and performance must be accompanied with larger number of pins supplying power to the IC, and hence competing with communication lines for resources and undermining offchip bandwidths of MPSoCs. Supplying high-voltage power from the board and performing on-chip power conversion close to the devices using switching regulators can partially address this issue while also providing better control of voltage levels supplied to individual blocks of the IC [3]. 3.…”
Section: Introductionmentioning
confidence: 99%
“…Research and development of CMOS switch dc-dc converter has been done in order to realize the CLPG [1]- [4], where the power inductor on chip must be realized. P. Hazucha et al [1] reported the hundreds MHz switching 90 nm-CMOS switch dc-dc converter using air core chip inductors with 6 nH inductance on package.…”
Section: Introductionmentioning
confidence: 99%
“…In order to apply the on-chip magnetic thin film inductor for dc-dc conversion application, the rating current is also important issue. N. Sturcken et al [4] developed an integrated voltage regulator using coupledmagnetic-core inductor, where they used two sets of four coupled power inductors on Si-interposer. The inductor topology was an elongated spiral with a Ni-Fe magnetic thin film core encasing the copper windings on the long axis.…”
Section: Introductionmentioning
confidence: 99%